The effect of psychological factors on Syrian refugees’ participation in lifelong education - Mehmet Fatih Karacabey; Kivanc Bozkus (Institute of Advanced Engineering and Science, 2019)
The purpose of this research was to determine the effect of psychological factors on Syrian refugees’ participation in lifelong education. The ex post facto co-relational causal design was employed in this research. A questionnaire form consisted of four scales was used to collect data from 297 refugees participated in lifelong education. The structural equation modeling analysis revealed that psychological factors affect participation in lifelong education and learning approaches played the biggest role in this effect. It was claimed that learning approach is a strong predictor of participation in lifelong education. The effect of locus of control on participation in lifelong education was medium while the effects of self-efficacy and self-worth were weak. Recommendations to education providers, decision-makers and researchers to align both formal and lifelong education curricula with the results were given.